26 SISTEM INFORMASI PENGOLAHAN DATA IKPM (IKATAN KELUARGA PELAJAR MAHASISWA) MUARA ENIM BERBASIS WEB MENGGUNAKAN PHP DAN MY SQL - Septa, Richard; Hamzah, Amir; Andayati, Dina (Jurnal Script, 2014)
ABSTRACTData processing information systems IKPM Muara Enimcan over comethe problems that arisein the utilization ofinformation, particularlydata processing IKPMMuara Enim. data processingbya computer-based data processingis the change ina dynamic andconstantly evolving or changing with the development of Muara enimI KPM increasingly large influence onthe problem of informationI KPM Muara Enim. This study will beconductedinI KPM Muara Enim, one of the studentsI KPM Muara Enimin Yogyakarta, data processing information system absolute mustoccur in a processing information systems, therefore the system will be built to be able to keep the system processing of data contained by the system. This multi-user applications in the form of data processing is veryi mportant more so in need ofa clear and precise informationin a data processing information, the Association of Students, Muara Enim that is needed information accuracy with this systemcan hopefullyreduce the existing problems in IKPM Muara Enim.Keywords: informationsystem, college studentsfamily ties, multi-user